ضوابط مصادر الفعل الثلاثي المجرد في القياس والسماع وأسسها في اللغة العربية : دراسة معجمية صرفية تحليلية - دومة، رجب علي رجب (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims to study the foundations of the sources of measured triple letter verbs, and the standards for the derived nouns of the triplet letter verbs in traditional usage. The study also explains the doctrines of classical scholars between standard rules and traditional usage and classification of the The derived nouns of triple letter verbs in Arabic language based on the measurement and the regulation of traditional usage. This topic is meant to revive the thresholds of scholars and contribution towards the study of the foundations of triple letter verbs between measurement standard and traditional usage in Arabic language with explanation of their efforts and explication of their views in the establishment of standard measurements, and the standards of traditional usage in triple letter in Arabic language, and its classification The derived nouns of the abstract triple letter that were contained in the literature of Taj al-ʻArus written by Zubaidi. This study used an analytical descriptive approach to achieve its objectives by describing the views of scholars on the issue of measurement and traditional usage in The derived nouns of abstract triple letters verbs that are compiled in the book; Taj al-ʻArus. This study is enhanced by numerical calculation so as to make accurate percentage. The study has accomplished most of what it sought out to do, and reached the conclusion that the derived nouns of the triple letter verbs do not influence the measurement of abstract triple letters, or infringe on it, except that it is attached to it. Sibawaihi also made one of the important criterias of standardization of measure and traditional usage of the present participle that revolves between the subject, reciprocal action, comparative verb, and hyperbolize verbs, in conjunction with Arabic meanings. This is because it has direct effect on measuring the derived nouns of triple letters verbs, and that the verb has predominant weight between the weights of the sources of the triple verb in the Arabic language. The study found that there are one hundred and twenty kinds of measures for traditional usage in the derived nouns of abstract triple letters verbs in the Quranic language.